2020
DOI: 10.7150/ijms.47024
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA Hsa_circ_0066755 as an Oncogene via sponging miR-651 and as a Promising Diagnostic Biomarker for Nasopharyngeal Carcinoma

Abstract: Background: Circular RNAs (circRNAs) represent a class of broad and diversified endogenous RNAs that regulate gene expressions in eukaryotes. Hsa_circ_006675 has been proven as an important circRNA molecule in nasopharyngeal carcinoma (NPC), however, its function still remains elusive. This study aims to discuss the biofunctions of hsa_circ_0066755 in NPC. Methods: We detected the expression levels of hsa_circ_0066755 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…The proliferation and migration of endometrial tissue outside of the uterus is a defining characteristic of endometriosis, although the details of the pathological progression remain largely unknown 23 . CircRNAs have been recognized as important molecules in various biological processes, and abnormalities in their abundance or function may contribute to many diseases 3 , 24 , 25 . Studies have shown the abnormal expression of circRNAs in endometriosis and indicated their value in the diagnosis of diseases 26 , 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The proliferation and migration of endometrial tissue outside of the uterus is a defining characteristic of endometriosis, although the details of the pathological progression remain largely unknown 23 . CircRNAs have been recognized as important molecules in various biological processes, and abnormalities in their abundance or function may contribute to many diseases 3 , 24 , 25 . Studies have shown the abnormal expression of circRNAs in endometriosis and indicated their value in the diagnosis of diseases 26 , 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The AUC (area under the curve) value for differentiating radioresistant patients from radiosensitive patients was 0.945, with a sensitivity of 90.24% and a specificity of 94.51% ( 45 ). Wang et al ( 46 ) observed a significant increase of hsa_circ_0066755 in the NPC patients' plasma with an AUC value of 0.904. Meanwhile, plasma hsa_circ_0066755 testing presented a comparable diagnostic accuracy to the magnetic resonance imaging (MRI) ( 46 ).…”
Section: Circulating Circrnas In Different Cancersmentioning
confidence: 99%
“…Wang et al ( 46 ) observed a significant increase of hsa_circ_0066755 in the NPC patients' plasma with an AUC value of 0.904. Meanwhile, plasma hsa_circ_0066755 testing presented a comparable diagnostic accuracy to the magnetic resonance imaging (MRI) ( 46 ). Thus, circRNA_000285 and circMYC represent diagnostic and prognostic value for NPC, while hsa_circ_0066755 exhibits merely diagnostic characteristic.…”
Section: Circulating Circrnas In Different Cancersmentioning
confidence: 99%
“…Multiple circRNAs have been demonstrated to be involved in HNC development through the regulation of the proliferation process ( Figure 1 ). CircATRNL1 ( 40 ), hsa_circ_0007059 ( 41 ), circRNA_002178 ( 42 ), hsa_circ_0046263 ( 43 ), hsa_circ_0005379 ( 44 ), circUHRF1 ( 45 ), circPVT1 ( 46 , 47 ), circHIPK3 ( 48 , 49 ), circRNA_0000140 ( 50 ), circRNA_100290 ( 51 ), circDOCK1 ( 52 ), hsa_circ_0055538 ( 53 ), circITCH ( 54 ), hsa_circRNA_101036 ( 55 ), circCCND1 ( 20 ), circMYLK ( 56 ), CDR1as ( 17 , 57 , 58 ), circPKD2 ( 59 ), circLARP4 ( 60 ), hsa_circ_0042666 ( 61 ), hsa_circRNA_100533 ( 62 ), circMDM2 ( 63 ), circ_0067934 ( 64 ), circRPMS1 ( 65 ), circ-ZNF609 ( 66 , 67 ), hsa_circ_0072387 ( 68 ), circRASSF2 ( 38 ), hsa_circ_0023028 ( 69 ), circCTDP1 ( 70 ), circ_0008450 ( 71 ), circMATR3 ( 72 ), hsa_circ_0057481 ( 73 ), circ_0001742 ( 74 ), circ_0000218 ( 75 ), circ_0001971 ( 76 ), circCORO1C ( 77 ), hsa_circ_0109291 ( 78 ), hsa_circ_0036722 ( 34 ), hsa_circ_0002203 ( 79 ) and hsa_circ_0066755 ( 80 ) are associated with tumor proliferation ( Table 1 ).…”
Section: Circrnas Are Associated With Proliferation In Hncmentioning
confidence: 99%
“…CircRNAs in HNC have important roles in HNC metastasis and invasion ( Figure 2 ). Hsa_circ_0007059 ( 41 ), circUHRF1 ( 45 ), circHIPK3 ( 48 ), circRNA_0000140 ( 50 ), circRNA_100290 ( 51 ), hsa_circ_0055538 ( 53 ), CDR1as ( 17 , 57 ), circPKD2 ( 59 ), circLARP4 ( 60 ), hsa_circ_0042666 ( 61 ), hsa_circRNA_100533 ( 62 ), circ_0067934 ( 64 ), circRPMS1 ( 65 ), circ-ZNF609 ( 66 ), hsa_circ_0072387 ( 68 ), circRASSF2 ( 38 ), hsa_circ_0023028 ( 69 ), circCTDP1 ( 70 ), circ_0008450 ( 71 ), circMATR3 ( 72 ), hsa_circ_0057481 ( 73 ), circ_0001742 ( 74 ), circCORO1C ( 77 ), hsa_circ_0004491 ( 37 ), circ_0001971 ( 33 ), circFLNA ( 99 ), hsa_circ_0001162 ( 100 ), circARHGAP12 ( 101 ), circCRIM1 ( 102 ), circEPSTI1 ( 103 ), hsa_circ_0109291 ( 78 ), circRNA_002178 ( 42 ), hsa_circ_0002203 ( 79 ) and hsa_circ_0066755 ( 80 ) are involved in the regulation of HNC invasion and metastasis ( Table 2 ).…”
Section: Circrnas Are Associated With Invasion and Metastasis In Hncmentioning
confidence: 99%